KONSEP DASAR PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI SEKOLAH - Rahmad Nauli Siregar (UIN SYEKH ALI HASAN AHMAD ADDARY PADANGSIDIMPUAN, 2017)
Basic Islamic education curriculum is the Qur'an and Hadith, but not explained in detail. In the Qur'an and Hadith The term curriculum is more directed at the points of material that will be taught to students. PAI curriculum orientation refers to the development of values, community needs, talents and interests of students, opportunities for workers, and adjustments to the development of science and technology. In planning the curriculum, the main ones are the goals to be achieved according to various parties, curriculum content to support the achievement of goals, strategies in developing the curriculum, and evaluation as a tool to measure learning completeness and achievement of goals.